Metal–Organic Frameworks for Water Harvesting from Air - Kalmutzki, Markus J.; Diercks, Christian S.; Yaghi, Omar M. (Advanced materials (Weinheim), 2018)
Water harvesting from air in passive, adsorption‐based devices holds great potential for delivering drinking water to arid regions of the world. This technology requires adsorbents that can be tailored for a maximum working capacity, temperature response, and the relative pressure range in which reversible adsorption occurs. In this respect, metal–organic frameworks (MOFs) are promising, owing to their structural diversity and the precision of their functionalization for adjusting both pore size and hydrophilicity, thereby facilitating the rational design of their water‐sorption characteristics. Here, chemical and structural factors crucial for the design of hydrolytically stable MOFs for water adsorption are discussed. Prevalent water adsorption mechanisms in micro‐ and mesoporous MOFs alongside strategies for fine‐tuning of their adsorption behavior by means of reticular chemistry are presented. Finally, an approach for the selection of promising MOFs with respect to water harvesting from air is proposed and design concepts for next‐generation MOFs for application in passive adsorption‐based water‐harvesting devices are outlined. Metal–organic frameworks (MOFs) hold great promise as adsorbents for water harvesting from air. Structural parameters influencing the hydrolytic stability of and mechanisms of water‐adsorption in MOFs are discussed, and methods for fine‐tuning the adsorption behavior by reticular chemistry are illustrated. The working principles for MOF‐based passive water‐harvesting devices are outlined and design aspects for next‐generation MOFs are proposed.